Development of Mathematical Model for Optimized Design of Fiber Optic Sensor Geometry Using Ray Tracing Technique - Supriya S. Patil (Technological Innovation in Engineering Research Vol. 3, 2022)
Fiber optic displacement sensors are widely used in industry due to advantages such as simple design, low cost and immune to RFI and EMI. Non-contact type fiber optic sensors are popularly known as retroreflective type of extrinsic sensors. Due to its inherent advantages, retro reflective extrinsic Fiber optic sensors (FOS) have been examined, statistically modelled, and tested for performance. This paper reports easy pathway to study, analyze and optimize the retroreflective extrinsic type FOS as a software tool ‘FOS Explore’. This tool was created utilizing the ray tracing technique and a generalized mathematical model of FOS. Sensor geometries can be set and performance characteristics can be examined. The software, which was created using MATLAB, allows users to input various fiber specifications and geometrical factors in order to determine the sensor’s layout. For ease of comprehension, the simulated results are presented in the form of a tabular display, particular plots, and cross sectional views of sensor geometry. This software program is used to examine and optimize multiple architectures based on performance factors such as sensitivity and linear operating range at certain non linearity, in addition to basic configuration.